2022
DOI: 10.1111/jbi.14380
|View full text |Cite
|
Sign up to set email alerts
|

The biogeography of warming tolerance in lizards

Abstract: Aim Many ectotherms are at risk from climate change as temperatures are increasingly exceeding their thermal limits. Many evaluations of the vulnerability of ectotherms to climate change have relied on statistical metrics derived from coarse‐scale climatic data, which may result in misleading predictions. By applying an integrative approach, we investigated geographical correlates of the vulnerability of lizards to climate change. Location Globally. Taxon Lizards. Methods We combined data on lizard thermal phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 88 publications
(189 reference statements)
0
10
0
Order By: Relevance
“…Under future climate change scenarios, the climatic conditions with high species richness were projected to shift to even more extreme (warmer and wetter) conditions (Figure 3). This gives cause for concern, given that tropical forest and desert lizards already live in environmental conditions that are close to their thermal limits (Sinervo et al, 2010) and that desert and temperate lizard species have been found to be less able to regulate their temperature in order to deal with heat stress than tropical species (Anderson et al, 2022). Reptiles cannot regulate their body temperature internally, hence they are strongly dependent on using solar energy captured by the environment to regulate their body temperature (Huey, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Under future climate change scenarios, the climatic conditions with high species richness were projected to shift to even more extreme (warmer and wetter) conditions (Figure 3). This gives cause for concern, given that tropical forest and desert lizards already live in environmental conditions that are close to their thermal limits (Sinervo et al, 2010) and that desert and temperate lizard species have been found to be less able to regulate their temperature in order to deal with heat stress than tropical species (Anderson et al, 2022). Reptiles cannot regulate their body temperature internally, hence they are strongly dependent on using solar energy captured by the environment to regulate their body temperature (Huey, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…However, such macroscale studies often do not account for microclimate exposures, since microclimate variability can dramatically influence exposure to temperature extremes (González‐del‐Pliego et al, 2020; Riddell et al, 2021). Indeed, macroclimate data can produce inaccurate estimates of warming vulnerability relative to fine‐scale climatic data (Anderson et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, macroclimate data can produce inaccurate estimates of warming vulnerability relative to fine-scale climatic data (Anderson et al, 2022).…”
Section: Warming Tolerance Latitudinal and Habitat Differencesmentioning
confidence: 99%
“…To improve SDMs, future studies should try to consider additional factors, such as biotic interactions (Schleuning et al ., 2020) and the reshuffling of species communities (Voskamp et al ., in prep), which might lead to a change in competitive balance (Ockendon et al ., 2014), altered predator-prey relationships (Harley, 2011) or changes in functional diversity ( Stewart et al, 2022 ) and thus the provision of ecosystem functions and services (Pecl et al ., 2017). While the above factors might improve climate change impact projections in the future, such modelling exercises will never reflect the truth, as a species’ response to climate change will be strongly influenced by behaviour, diel rhythm, thermoregulatory potential and microclimatic conditions (Anderson et al ., 2022). This complexity highlights the need for integrative approaches when investigating species’ responses to climate change (Hof, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…3). This gives cause for concern given that tropical forest and desert lizards already live in environmental conditions that are close to their thermal limits (Sinervo et al ., 2010), while desert and temperate lizard species have been found to be less able to regulate their temperature in order to deal with heat stress than tropical species (Anderson et al ., 2022). Reptiles cannot regulate their body temperature internally, so are strongly dependent on using solar energy captured by the environment to regulate their body temperature (Huey, 1982).…”
Section: Discussionmentioning
confidence: 99%